Enhanced Electrochemical Performance of Electropolymerized Self-Organized TiO2 Nanotubes Fabricated by Anodization of Ti Grid - Sugiawati, Vinsensia Ade; Vacandio, Florence; Galeyeva, Alina; Kurbatov, Andrey P.; Djenizian, Thierry (Frontiers in Physics, 2019)
Self-organized TiO2 nanotubes grown on Ti grid acting as anode for Li-ion microbatteries were prepared via an electrochemical anodization. By tuning the anodization time, the morphology and length of the nanotubes were investigated by scanning electron microscope. When the anodization time reached 1.5 h, the TiO2nts/Ti grid anode showed a well-defined nanotubes, which are stable, well adherent 90 nm with a length of 1.88 µm. Due to their high surface utilization, surface area and material loading per unit area, TiO2nts /Ti grid anode using polymer electrolyte exhibited a high areal capacity of 376 µAh cm-2 at C/10 rate and a stable discharge plateau at 1.8 V without using a polymer binder and conductive additive. The storage capacity of the TiO2nts/Ti grid after 10 cycles is fifteen times higher compared to previous reports using planar Ti foils.